Sociodemographic Determinants in Cervical Cancer Screening Among the Underserved West Texas Women - Brooke Jensen; Hafiz Khan; Rakhshanda Layeequr Rahman (Mary Ann Liebert, 2023)
Objectives: Pap smear screenings are associated with a 60% reduction in cervical cancer rates for women over the age of 40 years. West Texas presents a challenge for cervical cancer screening as demonstrated by some of the highest incidence and mortality rates of any region in Texas. This study examined the role of socioeconomic and sociodemographic factors in the nonadherence of underserved/uninsured women treated by Access to Breast and Cervical Cancer Care for West Texas (ABC24WT) in three regions with the goal of identifying barriers to screening and higher risk groups. Methods: ABC24WT Program database was queried from November 1, 2018, to June 1, 2021, for sociodemographic variables, screening history, and screening results to identify high-risk groups for outreach. Independent samples t-test, Pearson's chi square test, and logistic regression were used to detect significant relationships between variables. Results: There were 1,998 women from the ABC24WT Program included in the study. The program's rates of abnormal pap tests were 21.5% (Council of Government 1 [COG-1]), 8.1% (Council of Government 2 [COG-2]), and 9.6% (Council of Government 7 [COG-7]), all much higher than the nation's average of 5%. Women without recent cervical screening (5 or more years) represented 31.8% (n?=?183) of COG-1, 40.3% (n?=?132) of COG-2, and 49.5% (n?=?61) of COG-7. In addition, a lower baseline adherence rate was noted in women with reduced incomes (<$600 per month per person) than those with higher incomes (p?=?0.008). Non-Hispanic women were two times more likely to ?no-show? screening appointments than Hispanic women (odds ratio [OR]?=?2.01, 95% confidence interval [CI] 1.31?3.08). However, Hispanic women required two times more colposcopies and biopsies (OR?=?2.08, 95% CI 1.05?4.13). Conclusions: Hispanic race and poverty represent a high-risk category for cervical cancer and form an important target for community outreach in West Texas.